2018
DOI: 10.3389/fimmu.2018.00078
|View full text |Cite
|
Sign up to set email alerts
|

Core Fucosylation of the T Cell Receptor Is Required for T Cell Activation

Abstract: CD4+ T cell activation promotes the pathogenic process of systemic lupus erythematosus (SLE). T cell receptor (TCR) complex are highly core fucosylated glycoproteins, which play important roles in T cell activation. In this study, we found that the core fucosylation of CD4+ T cells was significantly increased in SLE patients. Loss of core fucosyltransferase (Fut8), the sole enzyme for catalyzing the core fucosylation of N-glycan, significantly reduced CD4+ T cell activation and ameliorated the experimental aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 46 publications
(56 reference statements)
4
82
0
Order By: Relevance
“…In the cancer microenvironment, blocking core‐fucosylation induces a T cell response. In contrast, in colitis and systemic lupus erythematosus increased core‐fucosylation is accompanied by an increased T cell activation and response . However, in both cases, core‐fucosylation inactivation may be a potential new therapeutic avenue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the cancer microenvironment, blocking core‐fucosylation induces a T cell response. In contrast, in colitis and systemic lupus erythematosus increased core‐fucosylation is accompanied by an increased T cell activation and response . However, in both cases, core‐fucosylation inactivation may be a potential new therapeutic avenue.…”
Section: Discussionmentioning
confidence: 99%
“…Since TGF‐β1 supplementation in Fut8 deficient mice rescued the emphysema‐like phenotype, it suggests supplementation with this cytokine as a potential treatment for patients. Remarkably, in vitro and in vivo studies, have shown that FUT8 depletion has a greater and more generalized impact on the immune system components and response . Fut8 −/− mice exhibited an imbalanced immune cell count with high levels of eosinophils and monocytes, as well as an affected response to bacterial lipopolysaccharide (LPS) stimulation with decreased IFN‐β production .…”
Section: The Immunological Impact Of Glycosylation Defects—an Update mentioning
confidence: 99%
See 2 more Smart Citations
“…This modification, referred to as core-fucosylation, is ubiquitous throughout mammalian tissues and represents an important step in the maturation of complex N-glycans within the Golgi apparatus. Core fucosylation modulates the activity of many cell surface receptors, including: TGFβ1R 1, 2 , EGFR 3 , BCR 4 , TCR 5, 6 , CD14-mediated TLR2/4 signalling 7, 8 , and PD-1 9 . It also modulates the affinity of ligands for their receptors, the most notable example being the role that core fucose plays in decreasing the affinity of immunoglobulin G (IgG) for FcγRIIIa 10, 11 .…”
Section: Introductionmentioning
confidence: 99%